2004
DOI: 10.1002/pbc.20131
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of moderate aplastic anemia in children

Abstract: When childhood MAA is treated with supportive care alone, 2/3 of patients progress to SAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 19 publications
(11 reference statements)
1
42
0
Order By: Relevance
“…When childhood non-severe AA is treated with supportive care, 67% of patients progress to develop severe AA, suggesting that it is important to consider early immunosuppressive therapy. 24 Our data indicate that immunosuppressive therapy is beneficial for some patients with non-severe AA. A previous Japanese study showed that the addition of G-CSF to immunosuppressive therapy increased the hematologic response rate after 6 months and reduced the relapse rate in adult patients with severe AA.…”
Section: Discussionmentioning
confidence: 62%
“…When childhood non-severe AA is treated with supportive care, 67% of patients progress to develop severe AA, suggesting that it is important to consider early immunosuppressive therapy. 24 Our data indicate that immunosuppressive therapy is beneficial for some patients with non-severe AA. A previous Japanese study showed that the addition of G-CSF to immunosuppressive therapy increased the hematologic response rate after 6 months and reduced the relapse rate in adult patients with severe AA.…”
Section: Discussionmentioning
confidence: 62%
“…Clinically, the course of moderate aplastic anemia is variable: some patients progress to severe disease, others remain stable and may not require intervention; regular transfusions may not be required. 89 Very few clinical trials have specifically addressed moderate disease. Immunosuppression can reverse moderate pancytopenia and alleviate transfusion requirements; ATG and cyclosporine are more effective in combination, 73 but in practice are often used sequentially.…”
Section: Treatment Immunosuppressionmentioning
confidence: 99%
“…These patients may have moderate AA, a less severe form of AA that can persist for months or years, progress to more severe disease, or even resolve spontaneously. 5,30,31 As some cases of moderate AA 5,30,31 and lowgrade MDS (e.g., the 5qÀ syndrome 32,33 ) never progress to 34,35 whereas hypoplastic MDS patients generally have higher bone marrow CD34 þ cell counts. 9,10,36,37 However, significant overlap in the CD34 percentages between these two disorders has precluded using this assay diagnostically.…”
Section: Discussionmentioning
confidence: 99%